FOURIER-TRANSFORM INFRARED SPECTROSCOPY STUDIES AND EVALUATION OF TOTAL PHENOLICS, FLAVONOIDS, AND ANTIOXIDANT ACTIVITY OF CLEOME GYNANDRA - RAMYA KUBER BANOTH; ASHWINI THATIKONDA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to evaluate the nature of chemical constituents, total phenolics, total flavonoids, and antioxidant activity of Cleome gynandra and their functional groups with the help of phytochemical, Fourier-transform infrared spectroscopy (FTIR) analysis, colorimetric assay, and 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay. Methods: C. gynandra of the Cleomaceae family is an annual herb. The dried leaves were powdered and extracted using Soxhlet apparatus by different solvents. Preliminary phytochemical analysis was carried out to identify the phytoconstituents present in the extract of C. gynandra, FTIR spectrum was scanned at the range of 4000-400 cm−1. The extracts were subjected to the colorimetric assay in triplicate manner to quantitative determination of total phenolic and total flavonoid content. Gallic acid and rutin used as standards to determine the total phenolic content and total flavonoid content. Antioxidant activity was evaluated using DPPH radical scavenging method. Results: Phytochemical analysis of the ethanolic extract of C. gynandra revealed the presence of alkaloids, phenolics, saponins, steroids, flavonoids, cardiac glycosides, and tannins. FTIR spectrum showed intense bands at 3679.18, 3616.63, 3317.34, 2943.67, 1634.01, 1360.20, 1036.71, and 778.04 cm−1 corresponding to N-H2, O-H stretch, aliphatic C-H stretch, C=O, C-H benzene, C-O stretch, and C-Cl. The total phenolic content was found to be 8.39 ± 0.0952 mg gallic acid equivalent/g and 66.76 ± 0.0333 mg rutin equivalent/g. The DPPH radical scavenging activity of ethanolic extract was showed more scavenging activity compared to ethyl acetate and n-hexane fractions. Conclusion: The present research work creates a platform to screen many bioactive chemical constituents present in C. gynandra to treat various diseases.